Tom Clancy command and control - Cameron, Marc; Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan novel., 2023)
"For a century, the Panama Canal has served as the path between the seas. Control of this vital waterway is the difference between free trade and chaos in world markets. So when Panamanian President Rafael Botero asks for a show of support against the socialist opposition, his old friend President Jack Ryan can't turn down an invitation to visit the country, but what seems like an ordinary opportunity to preach the values of democracy quickly turns into a nightmare when a full-blown coup d'état erupts. President Ryan and his Secret Service team are cut off and out of communication. In Washington, the Vice President is coordinating a military response, but there's still one more obstacle. One of the main forces behind the coup is the ruthless criminal organization known as the Camarilla. They've had their tentacles deep inside the plot to overthrow the government. All of their hard work has just presented them with an unexpected opportunity they can't resist - the chance to kill President Jack Ryan"--